2015
DOI: 10.4025/actasciagron.v37i3.16970
|View full text |Cite
|
Sign up to set email alerts
|

<b>The influence of rootstock and time of harvest on the fruit quality during storage of in two grapefruit cultivars

Abstract: ABSTRACT. The effects of the 'Cleopatra' mandarin and 'Swingle' citrumelo rootstocks and time of harvest on the quality of cold-stored (13°C and 90% R.H.) 'Ruby Red' and 'Star Ruby' grapefruit grown under the tropical conditions prevalent in Ceará state, Brazil, were evaluated. Fruit quality was assessed by mass loss and peel color, the percentage of juice, soluble solids, titratable acidity, pH, maturity index, and ascorbic acid content. The results suggested that 'Ruby Red' and 'Star Ruby' grapefruit present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Hybrid origin of genotypes can favor the polyploidization (Machado et al 2015;Guerra et al 2016). As reported by Carvalho & Silva (2013), Citrumelo expressed the highest per cent of polyembryony (18.8%), followed by Rangpur lime and Volkamer lemon (13.7%), Sunki mandarin (9.4%) and Trifoliate orange (3.2%).…”
Section: Spontaneous Polyploidymentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid origin of genotypes can favor the polyploidization (Machado et al 2015;Guerra et al 2016). As reported by Carvalho & Silva (2013), Citrumelo expressed the highest per cent of polyembryony (18.8%), followed by Rangpur lime and Volkamer lemon (13.7%), Sunki mandarin (9.4%) and Trifoliate orange (3.2%).…”
Section: Spontaneous Polyploidymentioning
confidence: 99%
“…The plants grafted on Cleopatra rootstocks (2x) were demonstrated higher tolerance to salt and drought, and it is a well-known chloride excluder (Cerda et al 1979); however, it is susceptible to nematodes (Chadha & Singh 1990). Fruit shows low levels of albedo breakdown (Treeby et al 1995) and low susceptibility to decay under storage (Ritenour et al 2004), but it shows high levels of weight loss during storage period (Alirezanezhad & Eamin 2006;Machado et al 2015). This rootstock is very much suitable for virgin soils (Hardy, 2004).…”
Section: Cleopatra Mandarin (C Reshni Hort Ex Tan)mentioning
confidence: 99%
“…Many studies have addressed the effect of rootstock on citrus fruit color. Machado, Costa, Teixeira & Costa (2015) found that rootstock impacted color development in 'Ruby Red' grapefruit. Indeed, while Cleopatra fruit developed a yellowish external color, Citrumelo fruit displayed a pinkish peel color.…”
Section: External Colormentioning
confidence: 99%
“…In the present study the external color was influenced by both harvest and rootstock and the interaction between these two factors was significant (Table 2). (Machado et al, 2015). Firmness is an important fruit quality parameter, but is not included in the current citrus quality standards.…”
Section: Effect Of Rootstock On External Color Firmness Total Soluble Solids and Aciditymentioning
confidence: 99%
See 1 more Smart Citation